Telephony application programming interface (TAPI) - Peterson, Anak Empading. (Universiti Malaysia Sarawak (UNIMAS), 2001)
Telephony Application Interface (TAPI) is one of the Application Programming Interface (API) developed by Microsoft Corporation. A call can be made using TAPI through computer to destination phone. Beginning with TAPI 1.0, Microsoft Corporation has released TAPI 2.0, TAPI2.1 and TAPI 3.0 which have different kind of application build in. However, now everyone try to develop their own TAPI. Therefore the intent of this project is to give an introduction on TAPI in general beside their architecture and hardware consideration.